Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.3748/wjg.v19.i10.1563
|View full text |Cite
|
Sign up to set email alerts
|

MDCT angiography to evaluate the therapeutic effect of PTVE for esophageal varices

Abstract: MDCT provides excellent visualization of cyanoacrylate obliteration in EV and their feeding veins after PTVE. It confirms that PTVE is effective for treating EVs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…CT angiography and EUS were previously used to evaluate the effectiveness of endoscopic therapy for eradication of esophageal varices . , as it allows to clearly show diameter of hepatic portal vein and its collateral circulation [18, 19]. It has also been reported that a number of factors were related with esophageal varices bleeding, including the diameter of esophageal varices, red sign, Child-Pugh score, model for end-stage liver disease score(MELD), diameter of portal vein, portal vein embolus, hepatic venous pressure gradient (HVPG) [20].…”
Section: Discussionmentioning
confidence: 99%
“…CT angiography and EUS were previously used to evaluate the effectiveness of endoscopic therapy for eradication of esophageal varices . , as it allows to clearly show diameter of hepatic portal vein and its collateral circulation [18, 19]. It has also been reported that a number of factors were related with esophageal varices bleeding, including the diameter of esophageal varices, red sign, Child-Pugh score, model for end-stage liver disease score(MELD), diameter of portal vein, portal vein embolus, hepatic venous pressure gradient (HVPG) [20].…”
Section: Discussionmentioning
confidence: 99%
“…PTVE predominantly embolizes the gastric coronary vein and short gastric vein to block the blood flow of varicose veins and stop bleeding, which is a proven method to treat portal hypertension and EVB (9,19). This method may increase portal vein pressure and bleeding rate, therefore, its clinical applications are limited.…”
Section: Discussionmentioning
confidence: 99%
“…The PTAE procedure was performed under radiological and sonographic guidance as previously described [15][16][17][18][19][20][21]. Before the PTAE procedure, ultrasonography was performed in all patients to determine the best access route to enter the portal venous system.…”
Section: Percutaneous Transhepatic Portographymentioning
confidence: 99%
“…Modified percutaneous transhepatic antegrade embolization (PTAE) with 2-octyl cyanoacrylate (2-OCA) was reported to be effective in the prevention and treatment of esophageal and gastric variceal bleeding in our previous studies [15][16][17][18][19][20][21]. The main feature of this technical results in 2 BioMed Research International the anterograde embolization of the varices with cyanoacrylate from the transhepatic catheter, which can permanently obliterate the varices and all feeding veins.…”
Section: Introductionmentioning
confidence: 99%